The Effect of Product Quality, Service Quality and Price Perception on Customer Satisfaction - Pandiangan, Ferawita; Nisa, Puspita Chairun (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Maintaining and increasing brand loyalty is crucial due to a decrease in product differentiation and an increase in market uncertainty so that brand loyalty becomes a measure of the company's business performance which has an impact on product market share. The purpose of this study is to determine how perceived price, product quality, and service impact coffee shop brand loyalty by considering the mediating role of customer satisfaction in order to contribute to the literature on these relationships. The population of this study is Starbucks coffee shop customers who live in DKI Jakarta, the number of which is not known. Respondents of this study were 100 respondents with the criteria of Starbucks coffee shop customers aged 17 - 42 who had shopping experience at least 2 times in the last three months. The analysis method used is Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of this study found that product quality, service quality and price perception can increase customer satisfaction and brand loyalty. Product quality, service quality, and price perception on brand loyalty can also be mediated by customer satisfaction. This research shows that coffee shops need to improve both product quality, service quality, and price perception so that coffee shops can achieve higher customer satisfaction and brand loyalty as a form of a strong foundation in the growth of coffee shops.